Beam-shaping device-free femtosecond laser plane-by-plane inscription of high-quality FBGs. (June 2023) - Li, Xingyong; Chen, Fengyi; Bao, Weijia; Wang, Ruohui; Qiao, Xueguang
Abstract: Fiber Bragg gratings (FBGs) fabricated by femtosecond laser point-by-point inscription suffer from insertion loss (IL) and polarization-dependent loss (PDL) which degrade their performances in optical communication and sensing. To solve this problem, we propose a new method to realize plane-by-plane (Pl-b-Pl) inscription of high-quality fiber Bragg gratings by using high refractive index (RI) oil. The focal volume of the laser beam can be "stretched" due to the dispersive effect of the high RI oil along the transverse direction of the fiber. Compared to the reported femtosecond laser Pl-b-Pl grating inscription method, the high RI oil for Pl-b-Pl grating inscription is a simple and efficient method without additional beam-shaping devices (e.g., optical slits and spatial light modulators). Using the proposed method, a high-quality FBG can be inscribed, which has a high reflectivity of 98.1% (the Bragg resonance attenuation of 17.23 dB), and a low short-wavelength loss of 0.84 dB, and a low insertion loss of 0.23 dB. Most importantly, the PDL of the grating is only 0.12 dB. Highlights: We propose to use high refractive index oil is used to realize femtosecond laser Plane-by-Plane fabrication of fiber Bragg gratings. This method does not need additional beam-shaping devices (e.g., optical slits and spatial light modulators). The fabricated fiber Bragg gratings have advantages of high reflectivity, low short-wavelength loss, low insertion loss, and low polarization-dependent. The FBGs fabricated by the proposed method have a low polarization correlation, which can improve the wavelength measurement accuracy for quasi-distributed fiber grating sensing systems such as temperature and strain.